Monitoring Early Stage of Rice Crops Growth using Normalized Difference Vegetation Index generated from UAV. (November 2019) - Rosle, R; Che'Ya, NN; Roslin, NA; Halip, RM; Ismail, MR
Abstract: Remote sensing is a tool to gather the information about an object or any phenomenon without direct contact or damaging the objects. This technology had numerous application and one of it is in agriculture. Unlike tradition agriculture practiced that difficult to execute and required a large number of man power, implementing this technology will increase the production yield of the crops and improved the agriculture sector in managing and controlling. Remote sensing were able to forecast the crop production, identified the crop type, assess the crop damage and monitoring its progress. Therefore, this research was conducted in order to monitor the early stage of growth of rice crop planted by the farmers in the paddy field using remote sensing. To do so, popular empirical vegetation index known as Normalized Difference Vegetation Index (NDVI) generated from unmanned aerial vehicle (UAV) was selected to monitor the changes of rice crop starting from the day it been planted until eleventh day of planted. Early stage of monitoring the crop growth using NDVI is a best approach to practice. Any damages that occur during this stage will affect the yield production and economy. Result from image analysis shown that NDVI were able to observe the rice crop growth and able to locate the damage part in the paddy plot. Fast action can be made by the farmers to counter attack the damage and treat the problematic points.